Dampak Kepuasan Kerja Dalam Peningkatan Kinerja Perawat Dengan Komitmen Organisasi Sebagai Variabel Intervening ( Studi Pada Perawat Rs Pku Muhammadiyah Gamping) - Jasuha Saufa; Tri Maryati (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to analyze how much influence of job satisfaction on performance with organizational commitment as intervening study variable on nurses at PKU MuhammadiyahGamping Hospital. This research was conducted at PKU MuhammadiyahGamping Hospital and the respondent in this research is all nurses who work in PKU MuhammadiyahGamping Hospital. The number of respondents used in this study was 138 nurses. Types of data used are primary data and data collection techniques using survey techniques with questionnaires. Data analysis in this research using SEM (Structure Equation Modeling) which operated with Program AMOS 22.0. Based on the result of the analysis, the result shows that job satisfaction has significant effect on organizational commitment, job satisfaction has no significant effect on employee performance, organizational commitment has significant effect on employee performance, job satisfaction has significant effect on employee performance through organizational commitment as intervening variable.